Whatsapp Chatbot Implementation for New Students University of Labuhanbatu - Hanggi Kurniawan; Mulya Al Fazar; Nur Rahma Fauziah; Yoan Yoan; Ibnu Rasyid Munthe (Jurnal Mantik, 2021)
The issue that frequently arises is that potential new students find it difficult to get information about the campus of their choice because the office and students are human beings who need rest and are not constantly on campus. As a result, a chatbot on the WhatsApp platform was created to make it simpler for prospective students to obtain information about campus, class schedules, and so forth.